2019
DOI: 10.11648/j.ajp.20190502.11
|View full text |Cite
|
Sign up to set email alerts
|

Application of Hemoadsorption in Neonatal and Pediatric Hyperinflammatory States: A Case Series

Abstract: Objective: Extracorporeal blood purification therapies are increasingly applied in the field of intensive care medicine. Compared to filtration-based methods mainly used for renal replacement therapy, newest adsorptive approaches have shown to specifically target the inflammatory cascade by the effective removal of relevant mediators. In the neonatal and pediatric setting however, the application of these methods brings with it various challenges but also profound technical difficulties. Recently, a promising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Out of the 163 clinical articles available in PubMed, 58 were identified that mentioned "catecholamines and/or vasopressors". In total, 25 papers were excluded; 12 because of non-comparability of the measurement scales [25][26][27][28][29][30][31][32][33][34][35][36]; 4 because the type and dose of vasopressors were not specified [37][38][39][40]; 1 that reported combined norepinephrine and epinephrine doses [41]; 1 that only reported on patients that had survived [42]; and 7 where there were no measurements pre-and post-adsorber use in the same patient [43][44][45][46][47][48][49]. The remaining 33 articles were summarized without considering different study designs or duration of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 163 clinical articles available in PubMed, 58 were identified that mentioned "catecholamines and/or vasopressors". In total, 25 papers were excluded; 12 because of non-comparability of the measurement scales [25][26][27][28][29][30][31][32][33][34][35][36]; 4 because the type and dose of vasopressors were not specified [37][38][39][40]; 1 that reported combined norepinephrine and epinephrine doses [41]; 1 that only reported on patients that had survived [42]; and 7 where there were no measurements pre-and post-adsorber use in the same patient [43][44][45][46][47][48][49]. The remaining 33 articles were summarized without considering different study designs or duration of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…We observed a marked decrease in inflammatory mediators, a reduction in catecholamine dosages and an improvement in organ functions, which was particularly pronounced in patients who survived. An early onset of treatment (at best within 24-48 hours after diagnosis of sepsis) seemed to be beneficial for eventual survival [1]. These results were not "our first aim or intention" when we applied Cytosorb for the first time.…”
Section: First Casementioning
confidence: 98%
“…The use of CytoSorb allowed us to obtain a rapid improvement of the hemodynamic conditions, the upgrading of renal and pulmonary functions, the reduction of vasopressors and the resolutive reduction of "cytochine storm" in several dramatic condition [1][2].…”
Section: First Casementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that PE in neonates results in improvement of multiple organ failure caused by septicemia [ 65 ]. Recently, as the new technology of extracorporeal PE hemoabsorption devices for cytokine reduction (such as Toraymyxin (Toray, Tokyo, Japan) [ 66 ] and CytoSorb (CytoSorbents Europe, GmbH, Berlin, Germany) [ 67 , 68 ]) has been introduced, contributing to the achievement of rapid hemodynamic stabilization in neonatal and pediatric patients with refractory septic shock. However, using PE in neonates is considered a challenge due to the relatively large extracorporeal blood volume in relation to the apheresis machines, which are developed for adults.…”
Section: Plasma Exchange As An Alternative To Exchange Transfusionmentioning
confidence: 99%